2021
DOI: 10.7326/m20-3799
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COVID-19 in Homeless Shelters

Abstract: Congregate living situations, such as homeless shelters, are high-risk settings for transmission of SARS-CoV-2 among residents and staff. This article describes findings from a study using active surveillance for SARS-CoV-2 that took place in 14 homeless shelters in King County, Washington, between 1 January and 24 April 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 23 publications
5
82
1
Order By: Relevance
“…Of the 43 studies that used PCR testing, 24 collected cross-sectional data and reported only the symptomatic status at the time of testing, so we could not distinguish between presymptomatic and asymptomatic cases ( 10–14 , 16 , 19 , 21 , 23 , 24 , 28–31 , 33–36 , 41–44 , 46 , 49 , 50 , 52 ). In these studies, the proportion of persons who tested positive but had no symptoms at the time of testing ranged from 40.7% to 100%, with a median of 75.5% (IQR, 50.3% to 86.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 43 studies that used PCR testing, 24 collected cross-sectional data and reported only the symptomatic status at the time of testing, so we could not distinguish between presymptomatic and asymptomatic cases ( 10–14 , 16 , 19 , 21 , 23 , 24 , 28–31 , 33–36 , 41–44 , 46 , 49 , 50 , 52 ). In these studies, the proportion of persons who tested positive but had no symptoms at the time of testing ranged from 40.7% to 100%, with a median of 75.5% (IQR, 50.3% to 86.2%).…”
Section: Resultsmentioning
confidence: 99%
“…This study offers a population-level assessment of how COVID-19 has affected people with a recent history of homelessness. Several previous reports from the United States have detailed case rates among people experiencing homelessness in the shelters of certain cities, with positivity among those tested ranging between 2% and 18%, 9 , 42 44 but they did not compare these rates with those in the general population. One report from Boston identified a cumulative case rate of 4.6% among people experiencing homelessness versus 0.19% in the general population over a 15-day period.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were instructed to place their self-collected nasal swabs directly into the UTM tube which was pre-labeled with a unique sample barcode. Next, participants were instructed to place the UTM tube containing the self-collected nasal swab into a specimen bag, pre-packaged with an absorbent sheet, and then to put the Samples were subjected to the SARS-CoV-2 assay in real-time if they were collected after February 25, 2020 and retrospectively if collected between January 1, 2020 and February 24, 2020 (Table A2) [19]. Samples with RNase P relative cycle threshold (C RT ) values ≤28 for the Open Array assay as recommended by Thermo Fisher, which has a preamplification step, and ≤36 for the SARS-CoV-2 assay were considered to contain sufficient material for pathogen detection (https://assets.thermofisher.com/TFS-Assets/LSG/manuals/MAN0017952_RespiratoryTractMicrobiotaProfiling_OA_AG.pdf).…”
Section: Data Collectionmentioning
confidence: 99%